The Feasibility of Development of Multi Split Model Based Hands On-Mind on Approach as Reconstruction Basic Literature and Character Value - Lily Thamrin; Dyoty Aulia Vilda Ghasya; Rio Pranata (STAI Hubbulwathan Duri, 2023)
This study aims to determine the feasibility of developing a multi-split model based on a hands on-mind on approach in elementary schools. The research method used is a mixed method, combining quantitative and qualitative methods in a series of studies. This research also uses RD (Research and Development), the Four-D development or 4-D models. The data source in this study was obtained from the results of the validation of the feasibility of developing a multi-split model based on a hands on-mind on approach which two experts in their fields validated. Product development in the form of a learning model,